1259. Bictegravir or Dolutegravir-Containing Antiretroviral Regimens in Solid Organ Transplantation: Single-Center Experience. (15th December 2022) - Sherman, Elizabeth M; Poon, Kenneth K; Eckardt, Paula A; Montalvo, Sheila; Bromberg, Romina J; Cevallos, Edison Cano
Abstract: Background: Solid organ transplantation (SOT) is the definitive treatment for end-organ failure in HIV-positive recipients. Bictegravir (BIC) or dolutegravir (DTG) based antiretroviral therapy (ART) is the preferred ART due to high efficacy, excellent tolerability and minimal drug interactions, yet there is a paucity of data on these second generation integrase inhibitors (INSTIs) in SOT. We report the Memorial Transplant Institute's experience using second generation INSTI-containing ART with or without emtricitabine/tenofovir alafenamide (FTC/TAF) in persons with HIV. Table 1. Demographics and clinical features of 16 patients with HIV undergoing solid organ transplantation (SOT). 3TC: lamivudine; AA: African American; BIC: bictegravir; DTG: dolutegravir; F: female; FTC: emtricitabine; H: Hispanic/Latino/a/x; IN: integrase; M: male; NH: Non-Hispanic/Latino/a/x; PR: protease; RPV: rilpivirine; RT: reverse transcriptase; SOT: solid organ transplantation; TAF: tenofovir alafenamide; W: white Table 2. Clinical course of 8 patients with HIV after solid organ transplantation (SOT). 3TC: lamivudine; ABC: abacavir; ART: antiretroviral therapy; ATV: atazanavir; BIC: bictegravir; c: cobicistat; DTG: dolutegravir; DRV: darunavir; eFGR: estimated glomerular filtration rate; ETR: etravirine; FTC: emtricitabine; r: ritonavir; RAL: raltegravir; RPV: rilpivirine; RTV: ritonavir; SOT: solid organ transplantation; TAF: tenofovir alafenamide Methods: This single-center observational study compiles data from medical records of all persons with HIV undergoing SOT seen by the Division of Infectious Disease from January 2017 through April 2022. We report clinical information and ART management of SOT candidates and recipients in our center. Results: Sixteen patients met inclusion criteria: 8 SOT candidates (7 kidney, 1 heart) and 8 SOT recipients (all kidney). Demographics are presented in Table 1. Patients were 63% male with a mean age of 55 years, CD4 323 cells/mm 3, and living with HIV for 16 years. ART regimens were BIC/FTC/TAF (50%), DTG/rilpivirine (RPV) (19%), DTG + FTC/TAF (19%) and RPV/FTC/TAF + DTG (6%), and DTG/lamivudine (6%). All pharmacokinetic enhancers were discontinued to avoid drug interactions with anti-rejection medications. Last on-treatment HIV RNA was < 200 copies/mL for 100% of patients. The clinical course of 8 post-renal transplant recipients is presented in Table 2. The most common post-SOT regimen was BIC/FTC/TAF. Post-SOT patients maintained HIV RNA < 200 copies/mL. No ART-related adverse effects were documented. Two allograft- or life-threatening infections and one episode of acute antibody rejection was reported. Expectedly, serum creatinine decreased and estimated glomerular filtration rate increased post-renal transplant. Conclusion: We provide additional insight into the use of BIC- and DTG-containing ART with or without FTC/TAF in the peri-SOT period. Our growing experience suggests second generation INSTI-containing ART regimens with or without FTC/TAF are effective and well tolerated following kidney transplantation. Additional research on the use of second generation INSTIs in the SOT patient population is needed. Disclosures: All Authors : No reported disclosures.